Pengembangan Aplikasi Media Pembelajaran Berbasis Website Untuk Materi Laju Reaksi di Tingkat SMA (Studi Pada SMA Brawijaya Smart School Malang) - Ignatius Chandra Christian; Ahmad Afif Supianto; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of the difficult material at the senior high school is the Reaction Rate, because students need to understand the factors that affect the Reaction Rate that are difficult if only explained verbally without being followed by practice. The problem is demonstrate the affect of the Reaction Rate requires time and effort. Learning books are considered to be lacking in representing factors of the reaction rate effectively. The teacher also has difficulty knowing the gap in understanding between students. Based on these problems, a learning media application is needed that can help teachers demonstrate the Reaction Rate material, know the level of understanding of students, are easily accessible and attract students' interest in learning. The methodology in this research uses Extreme Programming (XP) with the aim of covering all needs and changes in user needs. The design of the application is object oriented using the Model-View-Controller (MVC) design pattern.. The process of implementing the application is done using the CodeIgniter framework. Furthermore, the developed application was tested using the Basis-Path Testing and Compatibility Testing method to determine the level of successful implementation and User Acceptance Testing to determine user acceptance of the application. The results of the research indicate that the website-based Reaction Rate learning media application can accommodate needs and is easy to use by both teachers and students. Extreme Programming (XP) methodology is quite suitable to cover all needs, but for segmentation of learning media is less suitable because more changes occur in the user interface aspects.